FREQUENCY OF MATERNAL MORTALITY AND MORBIDITY IN PREGNANCY-INDUCED HYPERTENSION - Riaz, Shazia; Habib, Saadia; Jabeen, Alia (Journal of Ayub Medical College Abbottabad, 2011)
Background: Pregnancy-induced hypertension (PIH) is defines as hypertension in pregnancy, and is sustained blood pressure >140 mm Hg systolic or 90 mm Hg diastolic. Objective of this study was to see the maternal outcome in terms of morbidity and mortality in PIH. Methods: This descriptive study was conducted in Obstetrics and Gynaecology Unit of Fauji Foundation Hospital, Rawalpindi from January to December 2010. Both booked and un-booked cases were selected after fulfilling inclusion criteria. A detailed history and clinical examination was recorded and relevant investigations were performed. Patients were monitored for rise in blood pressure, development of complications related to hypertensions in pregnancy as well as maternal and perinatal outcome. Results: During this period, 100 patients were admitted with pregnancy-induced hypertension. Majority were un-booked. Primigravida were 60 (60%), and were in age group 21-30 year, remaining were above 30 year. Four patients had placental abruption, 2 pulmonary oedema, 5 HELLP syndrome, 2 severe renal impairment, 20 elevated liver enzyme, 23 uncontrolled blood pressure, 20 server preeclampsia, 10 thrombocytopenia, 3 eclampsia, 10 had impaired coagulation profile, and 1 had maternal death. Conclusion: Pregnancy induced hypertension is a major cause of maternal mortality and morbidity. In Pakistan, its incidence and related mortality are high due to lack of adequate antenatal care. Keywords: Maternal Mortality, Maternal Morbidity, Pregnancy